Relationship between Sexual Needs and the Quality of Life of Diabetes Mellitus Patients - Malik, Muh. Zukri; Mikawati, .; Purnamasari, Dewi (KnE Life Sciences, 2021)
Diabetes mellitus is a chronic disease that can cause serious complications and has a major impact on the quality of life experienced by sufferers. One of the effects of diabetes mellitus is a change in sexual identity and a person’s physical ability to carry out sexual activities. This study aims to determine the relationship between sexual needs fulfilment and quality of life experienced by Diabetes Mellitus patients. This research is a non-experimental quantitative study using a cross-sectional study approach, the population in this study were 49 diabetes Mellitus patients treated at the Labuang Baji Hospital. Data was collected using a questionnaire, sexual needs in women were assessed using the FSFI (Female Sexual Function Index) questionnaire and in men using the IIEF (International Index of Erectile Functions) while the quality of life was assessed using DQOL (Diabetes Quality Of Life). 57.7% of respondents felt their sexual needs were not met, and the quality of life of patients with diabetes mellitus 46.9% is poor. There is a relationship between sexual fulfilment and quality of life in diabetes mellitus patients at the Makassar Labuang Baji Hospital, Indonesia. Keywords: diabetes mellitus, sexual needs, quality of life